A pilot study of everolimus and radiation for neuroendocrine liver metastases. Issue 8 (21st June 2021) - Myrehaug, Sten; Chan, David L; Rodriguez-Freixinos, Victor; Chung, Hans; Hallet, Julie; Law, Calvin; Patel, Chirag; Milot, Laurent; Hudson, John; Chen, Hanbo; Singh, Simron
Abstract : Liver metastases are common in patients with neuroendocrine tumours. For patients, management must balance disease control with consideration of toxicity, given limited treatment options. Everolimus has demonstrated effectiveness in neuroendocrine neoplasms. Given emerging data of a synergistic effect with radiation therapy, we evaluated combined everolimus and radiation for neuroendocrine liver metastases. This single-arm, single-centre prospective pilot study evaluated the safety and efficacy of combined everolimus and radiotherapy for well-differentiated neuroendocrine liver metastases. Patients with unresectable liver metastases received everolimus for 30 days, followed by concurrent everolimus and liver radiotherapy, then a further 14 days of everolimus. Tolerability was evaluated using the CTCAE v.4.03. Individual metastasis response rate and local control were measured by RECIST v1.1. Overall survival, progression-free survival and freedom from a change in systemic therapy were estimated by the Kaplan–Meier method. Forty metastases were treated in 14 patients. No grade 3 or higher toxicities were identified in the concurrent treatment phase; one patient developed grade 3 toxicity in the post-radiation phase. Overall response rate was 38%. One- and 2-year local control were 97% and 71%. Median progression-free survival was 12 months. One- and 2-year overall survival were 100% and 92%. In conclusion, combined everolimus and radiation are well-tolerated for neuroendocrine liver metastases and are associated with excellent local control. The approach of selective local ablation of oligometastatic or oligoprogressive disease warrants further evaluation in this patient population.